The Evolution of Islamic Banking in Indonesia: Challenges, Opportunities, and Future Prospects - Rahmah, Zakiyah Zulfa; Fatmawatie, Naning Windarti; Yuliani, Yuliani; Syakur, Ahmad; Fatmah, Dinda; Putri, Karina Ananda; Hasani, Syaiful; Rahmah, Mirhamida; Rahmah, Yusriyah; Purnama, Chamdan; Syaipudin, Latif; Tohari, Ilham (INSTITUT AGAMA ISLAM SEBI, 2025)
This study aims to analyse the development of Islamic banking in Indonesia through a literature review approach. The study was conducted by examining scientific journals, books, official regulations, and reports from relevant authorities, which were then categorised thematically to provide a comprehensive overview. The results of the study show that Islamic banking has made significant progress since the establishment of Bank Muamalat Indonesia in 1992 to the formation of Bank Syariah Indonesia in 2021. This development is supported by regulations, including Law Number 21 of 2008, as well as authority policies that strengthen institutional structures. However, the market share of Islamic banking is still limited, public literacy is low, and the availability of competent human resources is inadequate. Nevertheless, growth opportunities are open through government support, digital transformation, and sustainable finance trends that are in line with Islamic principles. This study has limitations because it only uses literature review, so the findings are conceptual. Therefore, further studies are recommended to use empirical methods to assess the effectiveness of policies, digitalisation strategies, and the performance of Islamic banking compared to conventional banking. Penelitian ini bertujuan menganalisis perkembangan perbankan syariah di Indonesia melalui pendekatan kajian pustaka. Kajian dilakukan dengan menelaah jurnal ilmiah, buku, regulasi resmi, serta laporan dari otoritas terkait, yang kemudian dikategorikan secara tematik untuk memberikan gambaran menyeluruh. Hasil penelitian menunjukkan bahwa perbankan syariah telah mengalami kemajuan signifikan sejak berdirinya Bank Muamalat Indonesia pada tahun 1992 hingga terbentuknya Bank Syariah Indonesia pada tahun 2021. Perkembangan ini didukung oleh regulasi, termasuk Undang-Undang Nomor 21 Tahun 2008, serta kebijakan otoritas yang memperkuat struktur kelembagaan. Meskipun demikian, pangsa pasar perbankan syariah masih terbatas, literasi masyarakat rendah, dan ketersediaan sumber daya manusia kompeten belum memadai. Namun, peluang pertumbuhan terbuka melalui dukungan pemerintah, transformasi digital, serta tren keuangan berkelanjutan yang sejalan dengan prinsip syariah. Penelitian ini memiliki keterbatasan karena hanya menggunakan kajian literatur sehingga temuan bersifat konseptual. Oleh karena itu, studi lanjutan disarankan menggunakan metode empiris untuk menilai efektivitas kebijakan, strategi digitalisasi, dan kinerja perbankan syariah dibandingkan konvensional.